Study and Review of Problems and Obstacles Services Management Rule in Iran with Emphasis on HRM - Khosravi Nia, Shirko (2021)
The objective of this study was to study and review of problems and obstacles services management rule in Iran with emphasis on HRM. Which has been done in a descriptive method of field type and according to the opinion of experts. Statistical samples were selected through quotas. First, an interview was conducted with a statistical sample and then with Delphi method in three stages and exploratory factor analysis. Classifications in the civil service rule are made according to the characteristics of the system in seven categories. The results showed that system deficit, severe bureaucracy and neglect of the environment scored the highest. This factor can be divided into four categories of employment, employment and supply and maintenance of human resources. Ignoring the environment despite extensive communication is another factor. According to the results, it can be said that the civil service management rule in Iran for various reasons such as inflexibility, uncoordinated subsystems, static, lack of dependence and interaction of subsystems, etc. leads to different consequences in the input and output parts of the system in The administrative system of government agencies.